Possibility of produced and wastewater disposal in the process of Yurubcheno field development by methods of numerical physico-chemical simulation; SGEM. 15th International Multidisciplinary Scientific GeoConference; Bk. 1, Vol. 2 - Trifonov N. S. Nikolay Sergeevich (Hydrogeology, Engineering Geology and Geotechnics, 2015)
Title screen